Brand Image Strategy in Increasing the Number of New Students - Risma Aryanthi, Ayu; Novitawati, Novitawati; Noorhapizah, Noorhapizah (Journal of English Language and Education, 2025)
This study aims to analyze the brand image strategy implemented by PAUD IT Athaira in Banjarbaru City in increasing the number of students. In the midst of fierce competition between educational institutions, building an institutional image (brand image) is one of the important strategies to maintain its existence and attract public interest. The selection of the right method and relevant to the condition of the institution is a crucial factor in building a positive image, both internally and externally. Educational institutions need to formulate positioning, brand value, and marketing concepts that are able to reflect competitive advantages. This study uses a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The informants in this study include school principals and teachers. The results of the study show that the brand image strategy through the 7P marketing mix approach implemented by PAUD IT Athaira has a positive impact on increasing the number of students every year and increasing public awareness of the existence and quality of the institution. These findings show that a strategic and sustainable approach in building brand image has significant practical implications in strengthening the competitiveness of educational institutions in the modern era.